2020
DOI: 10.3329/baj.v22i2.47621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Tillage Options and Residue Retention for Sustainable Crop Production in Wheatmungbean- Rice Cropping Pattern in Dry Areas

Abstract: The study was conducted to know the productivity and soil fertility status of intensified rice-wheat (RW) systems by adding a third pre-rice crop mungbeani.ewheat-mungbeanrice cropping pattern. The trial comprises five packages of practices including crop residue retention, seeding methods with tillage options imposed on the component crops in the same cropping pattern. The results indicated that keeping standing 30% crop residue in the field with minimum disturbance of soil had significant contribution on gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Increased labour scarcity for agriculture owing to migration from rural to urban areas within and outside the country [8] is impacting on crop production worldwide. The MT requires less total labour requirements to achieve approximately the same crop production as of CT making MT more profitable over CT with lower production costs [9].…”
mentioning
confidence: 99%
“…Increased labour scarcity for agriculture owing to migration from rural to urban areas within and outside the country [8] is impacting on crop production worldwide. The MT requires less total labour requirements to achieve approximately the same crop production as of CT making MT more profitable over CT with lower production costs [9].…”
mentioning
confidence: 99%
“…Moreover, these systems exhibited significant increases in soil macro-nutrient availability, particularly potassium, further contributing to enhanced crop productivity. Complementing these findings, Hossain et al [25] reported the highest mean grain yield (4.39 t/ha) from raised beds with 30% residue retention systems, highlighting the importance of residue management in optimizing wheat yields. Conversely, conventional tillage practices resulted in lower yields (4.28 t/ha), attributed to reduced yield components.…”
Section: Impact Of Mechanized Crop Establishment Techniques On Wheat ...mentioning
confidence: 83%
“…The retention of crop residues was higher in Boro rice compared to monsoon (Aman) and pre-monsoon (Aus) rice and other crops (Akteruzzaman et al, 2012). On-farm research revealed that increased residue retention with minimum soil disturbance improved soil properties and yield of upland crops (Islam et al, 2014;Salahin et al, 2017;Hossain et al, 2019;Salahin et al, 2021). Crop residue retention on the top of the soil with any number of tillage systems plays a crucial role in improving agronomic productivity and environmental quality (Alam et al, 2016a;Salahin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%